Molecular Characterization and Immunological Evaluation of Truncated Babesia microti Rhoptry Neck Protein 2 as a Vaccine Candidate - Cai, Yu chun; Yang, Chun li; Hu, Wei; Song, Peng; Xu, Bin; Lu, Yan; Ai, Lin; Chu, Yan hong; Chen, Mu xin; Chen, Jia xu; Chen, Shao hong (Frontiers in Immunology, 2021)
Babesia microti is a protozoan that infects red blood cells. Babesiosis is becoming a new global threat impacting human health. Rhoptry neck proteins (RONs) are proteins located at the neck of the rhoptry and studies indicate that these proteins play an important role in the process of red blood cell invasion. In the present study, we report on the bioinformatic analysis, cloning, and recombinant gene expression of two truncated rhoptry neck proteins 2 (BmRON2), as well as their potential for incorporation in a candidate vaccine for babesiosis. Western blot and immunofluorescence antibody (IFA) assays were performed to detect the presence of specific antibodies against BmRON2 in infected mice and the localization of N-BmRON2 in B. microti parasites. In vitro experiments were carried out to investigate the role of BmRON2 proteins during the B. microti invasion process and in vivo experiments to investigate immunoprotection. Homologous sequence alignment and molecular phylogenetic analysis indicated that BmRON2 showed similarities with RON2 proteins of other Babesia species. We expressed the truncated N-terminal (33–336 aa, designated rN-BmRON2) and C-terminal (915–1171 aa, designated rC-BmRON2) fragments of the BmRON2 protein, with molecular weights of 70 and 29 kDa, respectively. Western blot assays showed that the native BmRON2 protein is approximately 170 kDa, and that rN-BmRON2 was recognized by serum of mice experimentally infected with B. microti. Immunofluorescence analysis indicated that the BmRON2 protein was located at the apical end of merozoites, at the opposite end of the nucleus. In vitro red blood cell invasion inhibition studies with B. microti rBmRON2 proteins showed that relative invasion rate of rN-BmRON2 and rC-BmRON2 group is 45 and 56%, respectively. Analysis of the host immune response after immunization and B. microti infection showed that both rN-BmRON2 and rC-BmRON2 enhanced the immune response, but that rN-BmRON2 conferred better protection than rC–BmRON2. In conclusion, our results indicate that truncated rhoptry neck protein 2, especially its N-terminal fragment (rN-BmRON2), plays an important role in the invasion of host red blood cells, confers immune protection, and shows good potential as a candidate vaccine against babesiosis.